Evaluation of Titanium Alloy Surface Roughness After Phosphoric Acid Etching - Wijaya, Livia; Suwandi, Trijani; Eddy, Eddy; Tjandrawinata, Rosalina; Erawati, Jeti; Pratiwi, Deviyanti (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
ABSTRACT Background: Tooth loss can be caused by periodontal disease, caries, and other factors. Dental implants made of titanium are a common solution to replace tooth loss. Titanium grade 5 (Ti-6Al-4V) is often chosen for an implant. Modern commercial implant surface roughness (Ra) ranges from 1 to 2 μm. Surface roughness has an important role in osseointegration. The acid etching method can be used to improve surface roughness. This study evaluates titanium alloy surface roughness after etching with varying concentrations of H3PO4 acid.Method: A laboratory experiment with a pre-test and post-test group design. 25 titanium alloy samples were divided into 5 groups (n=5) and treated with saline, HCl 37%, and H3PO4 acid 38%, 48%, and 58%. Surface roughness was measured using a surface roughness tester, while EDS and SEM tests analyzed titanium composition and surface characteristics.Result: The titanium used in this study is a titanium alloy. Surface roughness modification using acid had a higher roughness compare to saline with significant different (p<0.05). Surface roughness in the group H3PO4 48% and 58% had a lower roughness compared to HCl 37% but no significant different (p>0.05). Referring to the SEM results, each acid showed morphological changes on the surface and for saline there were no morphological changes.Conclusion: Varying concentrations of H3PO4 acid can effectively improve the surface roughness of titanium alloys, with solutions at 48% and 58% demonstrating similar effectiveness to 37% HCl acid.